Philippine Qualifications Framework and South Korea’s New Southern Policy: Towards Quality Tech-Voc Education - Inero Valbuena Ancho; Kadek Aria Prima Dewi PF (UHN IGB Sugriwa Denpasar, 2021)
This study is an attempt to revisit the Philippine Qualifications Framework (PQF) vis-à-vis South Korea’s New Southern Policy (NSP). The focus is on the tech-voc education given PQF mandates concerning NSP’s agenda. The PQF-NSP alignment in the context of tech-voc is emphasized as inputs are provided towards quality tech-voc education in the Philippines. This qualitative study uses policy document analysis as a methodology, primarily involving PQF and NSP. According to Cardno (2018), policy document analysis is a significant instrument for leaders in the education sector as it also functions as a research technique. Policies are accessed through retrieval from website searches (Patel, et al., 2017). Harmonizing mandates provisions, and agenda of the NSP and PQF provides clear-cut directions towards quality tech-voc education in the Philippines. Institutionalizing qualifications and standards through the PQF serve as a mechanism to complement existing practices not just in the country but in the ASEAN region as well. As PQF acts as an instrument to advance policy planning, creation, and implementation, the Philippines affirms its role in contributing to the region’s qualifications framework by gaining recognition and impact. This is a prime invitation for NSP to maximize and be an active partner in upholding quality and standards, and in this case, through the context of tech-voc education.